2022
DOI: 10.3390/ijms23074035
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Hydrogen Sulfide Regulation of Autophagy in Liver Disorders

Abstract: Autophagy is a complex process of degradation of senescent or dysfunctional organelles in cells. Dysfunctional autophagy is associated with many diseases such as cancers, immune dysfunction, and aging. Hydrogen sulfide (H2S) is considered to be the third gas signal molecule after nitrous oxide and carbon monoxide. In recent years, H2S has been found to have a variety of important biological functions, and plays an important role in a variety of physiological and pathological processes. In this review, we revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 99 publications
0
5
0
1
Order By: Relevance
“…19,20 Interaction between hypoxia and H 2 S H 2 S is believed to be the third gaseous signaling molecule which is widely expressed in mammalian cells and tissues. 21 Three enzymes are known to be involved in the production of endogenous H 2 S, namely cystathionine beta synthase (CBS), cystathionine gamma lyase (CSE), and 3-Mercaptopyruvate sulfotransferase (3-MST). 9 An increasing body of evidence has revealed the cross-talk between HIF-1 and H 2 S. In a study, knockdown of CSE was shown to affect H 2 S production, which impaired the stability of HIF-1α, suggesting that endogenous H 2 S is important for the regulation of HIF-1 signaling pathway.…”
Section: Adaptive Changes In Hhmementioning
confidence: 99%
See 1 more Smart Citation
“…19,20 Interaction between hypoxia and H 2 S H 2 S is believed to be the third gaseous signaling molecule which is widely expressed in mammalian cells and tissues. 21 Three enzymes are known to be involved in the production of endogenous H 2 S, namely cystathionine beta synthase (CBS), cystathionine gamma lyase (CSE), and 3-Mercaptopyruvate sulfotransferase (3-MST). 9 An increasing body of evidence has revealed the cross-talk between HIF-1 and H 2 S. In a study, knockdown of CSE was shown to affect H 2 S production, which impaired the stability of HIF-1α, suggesting that endogenous H 2 S is important for the regulation of HIF-1 signaling pathway.…”
Section: Adaptive Changes In Hhmementioning
confidence: 99%
“…49 In addition to causing endothelial dysfunction, homocysteine has been shown to cause contraction of HSC. This homocysteine-induced contraction of HSC is reversed by H 2 S. 21 HSC contraction is associated with regulation of liver sinusoidal blood flow and intrahepatic resistance, and it is hypothesized that H 2 S may be involved in regulating HSC contraction together with LSEC-derived paracrine cytokines. 21 Briefly, reduced levels of H 2 S in the portal microcirculation cause an increase in intrahepatic resistance, not only because it is part of endothelial dysfunction, but also because it facilitates the activation and contraction of HSC.…”
Section: Vasodilatory Effects Of H 2 S In Portal Hypertensionmentioning
confidence: 99%
“…In addition, L-cystine can be converted into 3-mercaptopyruvate (3-MP) catalyzed by cysteine aminotransferase (CAT) by transferring amine to α-ketoglutarate to form 3-mercaptopyruvate (3-MP). Finally, 3-MP can be converted into H 2 S catalyzed by 3-MST (Figure 2) [32][33][34]. Studies have shown that H 2 S is involved in various physiological processes, including inflammatory response, energy metabolism, oxidative stress, mitochondrial biogenesis, and neuroregulation [35][36][37][38].…”
Section: Overview Of Hydrogen Sulfidementioning
confidence: 99%
“…After carbon monoxide (CO) and nitrous oxide (NO), hydrogen sulfide (H 2 S) is the third gaseous signal molecule associated with smooth muscle relaxation in the vascular system [ 67 ]. H 2 S has other important biological functions and is involved in various human diseases, including MAFLD [ 68 ].…”
Section: Autophagy In Mafldmentioning
confidence: 99%